Literature Review: Integrasi Nilai Budaya Festival Tabut Bengkulu dalam Kurikulum Merdeka sebagai Penguatan Karakter Peserta Didik - Apriliana, Laila Dwi; Nurlela, Leni; Indriani, Rina (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
This research aims to determine the potential for integrating cultural values from the Bengkulu Tabut Festival in the independent curriculum as an effort to strengthen students' character. The method used is a Literature Review by analyzing how these cultural values can be adapted in learning that supports the Pancasila Student Profile. Based on the research results, it was found that local regional cultural values have an important role in shaping the character of students. Students will gain insight into the potential of a region, recognize the value of local wisdom, and internalize values if regional potential is integrated and be able to make students have character. Character formation based on the Pancasila Student Profile in the Independent Curriculum can be done by strengthening local wisdom values such as the Tabut Festival which is applied in intracurricular and extracurricular learning. By integrating cultural values at the Tabut Festival, the character of the Pancasila student profile can be realized in the form of working hard, independent, creative, innovative, honest, hard working, persistent, caring for the environment, and many more, thus making students more familiar with the local wisdom of their region.